Aid effectiveness, debt relief and public finance response: Evidence from a panel of HIPCs - Danny Cassimon; Bjorn Van Campenhout (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Substantial amounts of debt relief have been granted to a set of low-income countries, as an alternative aid modality. Although the theoretical case for debt relief is firmly established, only empirical analysis can show whether debt relief is indeed a (more) effective mode of aid delivery. We investigate the linkages between debt relief and other fiscal variables such as current expenditure, government investment, taxation and domestic borrowing, in comparison to the effects of grants and concessional loans. We find that the fiscal impact of HIPC debt relief follows fairly complex dynamics. For example, debt relief initially reduces government investment, but the effect becomes positive after two years, well outperforming other modes of aid delivery. – HIPCs ; debt relief ; fiscal response ; aid effectiveness
Keywords: F34; F35; O11; O19; 330; Schuldenerlass; HIPC; Entwicklungshilfe; Öffentliche Finanzwirtschaft